Case Report: De novo variant in myelin regulatory factor in a Chinese child with 46,XY disorder/difference of sex development, cardiac and urogenital anomalies, and short stature - Wang, Hui; Wu, Dian; Wu, De-Hua; Tian, Hong-Juan; Li, Hai-Feng; Jiang, Ke-Wen; Zou, Chao-Chun (Frontiers in Pediatrics, 2022)
The myelin regulatory factor (MYRF; MIM# 608329) gene was first identified as a key transcription factor involved in oligodendrocyte differentiation and central nervous system myelination. With the recent development of exome sequencing, pathogenic variants of MYRF have been described in syndromic forms of cardiac-urogenital syndrome (CUGS), 46,XY and 46,XX disorders of sex development (DSDs), and nanophthalmos manifestations. Herein, we describe a 4-year-7-month-old girl with ventricular septal defect, atrial septal defect, patent ductus arteriosus, severe pulmonary hypertension, moderate-to-severe tricuspid regurgitation, enlarged coronary sinus, left superior vena cava, and right lung hypoplasia at birth. Later, the patient developed short stature and amblyopia. Further examination revealed karyotypes of 46,XY and visible uterus, whereas the ovary and testis were not explored. Laparoscopy revealed dysplasia of testicular gonads. Whole-exome sequencing (WES) was performed and a de novo heterozygous mutation in MYRF was identified, known as c.2817G>A/p. W939* (NM_001127392.3). Therefore, this case report presents multiple clinical manifestations with syndromic symptoms of CUGS, 46,XY DSD, and ocular symptoms. These new data expand the phenotype of the MYRF variant and may assist in more accurately delineating the phenotypes caused by the variants of this gene.